Computational Studies of Budesonide vs. Vilanterol: Asthma Drugs Against SARS-CoV-2 Mpro - Hussain, Afzal; Hussain, Ashfaq (Current Chinese Science, 2022)
The global spread of SARS-CoV-2 and the mortality it has caused have prompted research organizations to develop novel medications to combat COVID-19 infection. The main protease (Mpro) of SARS-CoV-2 is crucial for the virus's replication and propagation in host cells. Therefore, it is a promising therapeutic target. There are officially no certified specific drugs or available interventions for COVID-19 infection. Repurposing standard pharmaceutical drugs for COVID-19 interventions is a promising way of identifying potent therapeutic candidates quickly. In this work, vilanterol over budesonide was studied using molecular docking, ADMET, and MMGBSA analysis via Schrodinger Software to find more potent drugs that can diminish the risk of rigorous SARS-CoV-2 infection and shorten the time to recovery. We have identified that vilanterol showed more promising potential as an inhibitor of COVID-19 Mpro than budesonide (studied by the University of Oxford). Vilanterol has indicated a docking score of -8.727, human oral absorption of 88.786%, and the free binding energy of -60.457, whereas budesonide presented a docking score of -6.077, human oral absorption of 83.863, and the free binding energy of -36.078. Finally, our computational strategy identified vilanterol over budesonide as a promising and efficacious SARSCoV- 2 inhibitor that could be investigated further in clinical trials.
Keywords: budesonide